Numerical simulation of horizontal rigid submarine landslide generated tsunami using FLOW-3D HYDRO model - Van Khoi, Pham; Hong Hanh, Nguyen Thi; Van Nghi, Vu (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
This study presents a comprehensive numerical simulation of tsunamis generated by horizontal rigid submarine landslides using the FLOW-3D HYDRO model. Submarine landslides are critical geo-hazards that can trigger destructive tsunamis, posing severe risks to coastal communities. Unlike deformable landslides, rigid landslides maintain structural integrity, transferring energy more efficiently into the water column and producing distinctive, high-amplitude waves. The FLOW-3D HYDRO model, with its advanced capability to simulate multiphase flows and solid-fluid interactions, is used to explore these dynamics, focusing on the effects of slide velocity, slope angle, and water depth. Experimental data are used to validate the model, confirming its accuracy in reproducing observed wave dynamics. The results reveal that horizontal rigid submarine landslides generate waveforms with rapid onset and high initial amplitudes, which intensify near the shore. This research underscores the importance of high-resolution modeling to improve tsunami hazard assessments, especially for near-field events with limited early-warning timeframes. The insights from this study contribute to the development of more reliable early-warning systems and better-informed coastal defense strategies for mitigating tsunami impacts.